1983
DOI: 10.1002/j.2050-0416.1983.tb04217.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Malt ‘Friability’ and Wort Viscosity

Abstract: There is accumulating evidence relating brewhouse performance of malt to either the p-glucan content of the malt or to aspects of wort viscosity. Malts are occasionally found with adequate standard analyses yet produce worts with higher than average viscosities. The 'Friabilimeter' has been used to investigate the properties of such malts. It has been demonstrated that, in many cases, wort viscosity is strongly influenced by small proportions (<5%) of water sensitive grains which fail to germinate properly, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…All the materials were grown in the field of the Tochigi branch of the Tochigi prefectural agricultural experiment 1 station in 2002-2003. Plants were spaced 10 cm apart within rows, and rows were spaced 65 cm apart.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the materials were grown in the field of the Tochigi branch of the Tochigi prefectural agricultural experiment 1 station in 2002-2003. Plants were spaced 10 cm apart within rows, and rows were spaced 65 cm apart.…”
Section: Plant Materialsmentioning
confidence: 99%
“…To make high quality breeding efficient, a quick quality estimation method that involves the use of grain or malt itself is required. To meet this requirement, a friabilimeter that uses malt for the prediction of EX and VI, and a pearlograph using malt for hot water extract have been developed and used in breeding 1,5,12 . A Single Kernel Characterization System 4100 (SKCS) has also been used in recent times for cereal quality estimation using grains of barley, wheat, rice, oats and sorghum 2,7,8,10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…It was also noted that malt acidified with L. plantarum TMW 1.460 had a higher glassy corn fraction than all other malt samples. Numerous studies have examined the relationship between malt friability and wort viscosity, and reported strong negative relationships between the aforementioned parameters 6,47 . Our results do not support these findings as malt acidified with L. plantarum TMW 1.460, had the lowest friability, and a low wort viscosity.…”
Section: Friabilitymentioning
confidence: 99%
“…Conventionally, the presence of β ‐glucan content in the MLR was expected since the levels of this polysaccharide have been associated with wort viscosity and are the primary cause of reduced filtration efficiency during the brewing process . Friability also has a minor but significant role in predicting wort viscosity related to the modification of malt cell walls . β ‐Glucan and friability were, however, minor predictors compared with xylanase in this investigation, which suggests the functional importance of measuring this enzyme when assessing malt quality.…”
Section: Resultsmentioning
confidence: 64%